Preparation of a novel CeO/SiO adsorbent and its adsorption behavior for fluoride ion - Jin Lin; Yan Wu; Afshin Khayambashi; Xiaolong Wang; Yuezhou Wei (Adsorption Science & Technology)
The silica-based CeO 2 adsorbent (CeO 2 /SiO 2 ) was prepared for removing fluoride from the aqueous solution. The synthesized adsorbent was characterized by scanning electron microscope, energy dispersive spectrum, X-ray diffractometer, Fourier transform infrared spectrometer, and zeta potential measurement analyses. The adsorption batch experiments in the various experimental conditions including solution pH, contact time, initial fluoride concentration, and adsorption temperature were performed and investigated. The maximum adsorption capacity of fluoride into CeO 2 /SiO 2 was 2.441 mmol/g at pH 3 and 298 K. The adsorption kinetics and isotherms were well described by the pseudo-second-order model and the Langmuir model, respectively. The fluoride adsorption reached the equilibrium in 15 min from the aqueous solution with the initial fluoride concentration of 400 mg/l at 298 K. In the temperature range of 298–338 K, the maximum adsorption capacity of fluoride decreased from 2.441 mmol/g to 2.109 mmol/l at pH 3. The adsorption thermodynamics study revealed that this process was a spontaneous, exothermic, and entropy-driving adsorption. Furthermore, the mechanism of adsorption was identified as the anion exchange and the electrostatic interaction. The desorption efficiency of fluoride-loaded CeO 2 /SiO 2 adsorbent could reach about 95% by 0.1 mol/l NaOH.